Circulating fibroblasts and neutrophils co-expressing CDH11+ and chemokine receptors in rheumatoid and psoriatic arthritis: a shared mechanism of ‘arthritis spreading’? - Kyriakidi, Maria; Vetsika, Eleni-Kyriaki; Fragoulis, George E.; Sakkou, Maria; Verrou, Kleio-Maria; Mourikis, Anastasios; Vlachogiannis, Nikolaos I.; Tektonidou, Maria G.; Sfikakis, Petros P. (Frontiers in Immunology, 2026)
BackgroundThe mechanisms underlying the progression of chronic inflammatory arthritis remain largely unclear.MethodsWe used single-cell mass cytometry on peripheral blood from patients with active rheumatoid arthritis (RA; n=11), psoriatic arthritis (PsA; n=12), and controls (n=9) to identify circulating cells co-expressing mesenchymal markers, including the homotypic adhesion molecule cadherin-11 (CDH11), and chemokine receptors. Proteomic profiling was performed on matched plasma using Olink. Confocal microscopy was used to investigate cell localization in synovial tissue.ResultsCirculating cells co-expressing mesenchymal markers, including the adhesion molecule cadherin-11 (CDH11) and chemokine receptors, were identified. Of them, circulating fibroblasts (podoplanin+CD45-CD3-CD19-CD4-CD8-CD56-CD66b-CD294-) co-expressing CDH11 and C-C Chemokine Receptor 7 (CCR7) were found exclusively in arthritis patients’ blood. These cells were not detected in paired bone marrow samples, suggesting their potential origin from inflamed joints. Increased circulating fibrocytes (CD34+HLA-DR+CD45+CD3-CD19-CD4-CD8-CD56-CD66b-CD294-) co-expressing CDH11 and CCR7 were also found in patients’ blood. These cells were more prevalent in bone marrow, supporting their bone marrow origin. Among various leukocyte subsets, CDH11+CD90+CCR6+neutrophils were markedly elevated in both RA and PsA. These populations persisted after 3 months of antirheumatic drug administration, regardless of treatment response. Proteomic profiling on matched plasma using Olink, revealed that the presence of circulating CDH11+fibroblasts was associated with higher C-X-C Motif Chemokine Ligand 1 (CXCL1), Angiopoietin 1 (ANGPT1) and Tissue Inhibitor of Metalloproteinase 3 (TIMP3) levels, proteins involved in angiogenesis, chemotaxis, and matrix remodeling, respectively. Moreover, in patients with detectable circulating CDH11+fibroblasts chemokine signaling and cell-substrate adhesion were enriched. Finally, CDH11+neutrophils were identified in close proximity to synovial fibroblasts by confocal microscopy in knee-surgery-obtained rheumatoid synovium.ConclusionsCombining our findings with previous data showing circulating pre-inflammatory mesenchymal cells preceding rheumatoid arthritis flares, we propose that a chemokine-orchestrated process, that seems to not being affected by short-term Disease-Modifying Antirheumatic Drug (DMARD) treatment, may contribute to ‘arthritis spreading’ in both RA and PsA. In this chronic process synovial fibroblasts and fibrocytes with pathogenic potential may migrate into distant synovium through CDH11-mediated homotypic binding.